Occurrence of frogs in a non-forest area of Similajau National Park, Bintulu, Sarawak - Saripuddin, Noor Bahiah; Hassan, Mohd Zafri; Muhd Sahimi, Hani Nabilia; Mohd Top @ Mohd Tah, Marina (2015)
A survey on the occurrence of frogs in non-forest area at Similajau National Park (SNP) was carried out from August 2014 until January 2015. Transect line and quadrat methods were used to sample frogs in the area. A total of 193 individuals of nine species belonging to the families of Dicroglossidae, Ranidae and Rhacophoridae were detected and counted. No endemic and new species were recorded from the study. The survey area was dominated by the crab-eating frog, Fejervarya cancrivora (30.6%) and the Asian grass frog, Fejervarya limnocharis (25.4%), both of which are of family Dicroglossidae. All recovered species were least concern under IUCN Red List of Threatened Species, 2014, except for lesser swamp frog, Limnonectes paramacrodon and the Malayan flying frog, Rhacophorus rufipes that have been classified as near threatened. The results from this study showed that although the non-forest area of SNP consisted of common frogs found in other tropical area, the species diversity is still relatively higher than elsewhere.